Pengaruh Motivasi Intrinsik dan Keterlibatan Kerja Terhadap Kinerja Pegawai Pada Kantor Pemerintahan Kecamatan Sibolga Selatan Kota Sibolga - Syarifah Eryanti Tanjung; Yenni Sofiana Tambunan; Muhammad Iqbal Batubara (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of intrinsic motivation and job involvement on employee performance, both partially and simultaneously, at the South Sibolga District Government Office, Sibolga City. This research employed a quantitative approach with a descriptive method, involving the entire population as a sample of 65 respondents using a saturated sampling technique. Data analysis was conducted using multiple linear regression. The results show that intrinsic motivation and job involvement simultaneously have a positive and significant effect on employee performance, contributing 56% to performance variation. Partially, intrinsic motivation has a significant effect on employee performance, while job involvement is the most dominant variable influencing performance. The regression model indicates a positive relationship between independent and dependent variables, implying that increasing intrinsic motivation and job involvement will improve employee performance.